2007
DOI: 10.1007/s11244-007-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare earths based oxides as alternative materials to Ba in NOx-trap catalysts

Abstract: The reduction of NOx from Diesel Engines is a major issue of automotive catalysis. In this paper, we investigate basic rare earths oxides (such as La 2 O 3 , Nd 2 O 3 or Pr 6 O 11 ) used as NOx-trap sites in replacement of Ba. These species are intimately mixed with (CeZr) solid solutions and the thus obtained mixed oxides are considered as Pt carrier. Investigations on powder model Pt-(CeZr)/RE 2 O 3 (or Pr 6 O 11 ) catalysts show promising results. These model catalysts present high NOx storage capacity, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
(5 reference statements)
0
17
0
Order By: Relevance
“…Indeed, a study by Rohart and co-workers [20] found that doping 8 wt% Pr into a Ce-Zr mixed oxide resulted in a significant increase in the efficiency of NOx storage (for samples loaded with 1 wt% Pt), particularly at lower temperatures ºC). This increase was found to correlate with improved activity for NO oxidation over this temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a study by Rohart and co-workers [20] found that doping 8 wt% Pr into a Ce-Zr mixed oxide resulted in a significant increase in the efficiency of NOx storage (for samples loaded with 1 wt% Pt), particularly at lower temperatures ºC). This increase was found to correlate with improved activity for NO oxidation over this temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in ceria-praseodymia solid solutions, both elements can adopt 3+ and 4+ oxidation states, and the anionic vacancies are highly mobile in this system. Thus, the insertion of praseodymium within the fluorite host lattice of CeO2 provides new materials with improved catalytic properties for environmental applications, such as automotive three-way catalysts [6,7], NOx trap catalysts [8], N2O decomposition [9,10], (preferential) CO oxidation [11][12][13], volatile organic compounds combustion [13][14][15] and soot removal [16][17][18]. These studies showed that the CexPr1-xO2-δ mixed oxides can undergo more oxygen exchange than pure ceria at lower temperatures and that they are more promising catalysts than other trivalent rare-earth substituted ceria formulations.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are few reports about the addition of rare earth oxides into CZA supports for NO x elimination. [23][24][25] In our continuous efforts to seek highly stable and efficient NSR catalysts, [26] herein, we report the synthesis and properties of a series of rare-earth-doped catalysts, Pt/Ba/RO-…”
Section: Introductionmentioning
confidence: 99%